Pharmaceutical chemistry : Drug design and action - Campos Rosa, Joaquín M. (Berlin: De Gruyter, 2024)
The Second Edition has been thoroughly revised with a modern look. The chapters on QSAR and Drug Metabolism have been extended, emphasizing concepts, such as the hyperconjugative effect or the anomeric effect, in which the student normally finds it difficult to understand. Stereoelectronic effects are essential to explain the mechanism of action of drugs and therefore, its agile and intuitive handling will allow the student access to both chemical and biological mechanisms, in a more rational way. The text is illustrated with hundreds of formulas and many tables that facilitate the understanding of this interesting discipline, which is halfway between Organic Chemistry, Biochemistry and Pharmacology. This Volume is aimed at building basis principles on drug design and it is likely to be of interest to students reading, pharmacy, pharmacology, and pharmaceutical chemistry.
Includes bibliographical references (page ix) and index.
Keywords: Pharmaceutical chemistry; Drug development; Drugs Design; Pharmacodynamics; Medicinal chemistry